Development of the Logistics System of the Air Transport Complexes of the Southern Federal District ("Journal "U". Economy. Management. Finance.", 2017)
In this article the author examines the prospects for logistics development of the air transport complexes in the Southern Federal district as the most priority directions of ensuring the stable and efficient operation of the transport system of the region, which finally leads to the advancement of the region in the market of international transit of goods.
Keywords: Southern Federal District; logistic system; air transport; air transport complex